Linguistic and Cultural Analysis of Empathy: Strategies for Japanese-English Translation - Becker, Anne (Curtin University, 2018)
Examining linguistic and pragmatic aspects of the translation of Japanese empathy and politeness in contemporary novels reveals that socio-cultural meaning is often neutralised. From an educational perspective, examples for intercultural language teaching and learning, universal and culturally specific values, and the attribution of meaning in collectivist and individualist societies can be examined. Implications for the viability of a universal approach to translation are discussed in relation to values that are specific to Japanese culture.